multiply the polynomial expression (x + 2)( x - 4)

1 answer

To multiply the polynomial expressions \((x + 2)(x - 4)\), you can use the distributive property (also known as the FOIL method for binomials):

\[ (x + 2)(x - 4) = x(x - 4) + 2(x - 4) \]

Now, distribute each term:

  1. \(x \cdot x = x^2\)
  2. \(x \cdot (-4) = -4x\)
  3. \(2 \cdot x = 2x\)
  4. \(2 \cdot (-4) = -8\)

Now, combine all the terms:

\[ x^2 - 4x + 2x - 8 \]

Combine like terms:

\[ x^2 - 2x - 8 \]

So, the result of the multiplication is:

\[ \boxed{x^2 - 2x - 8} \]